The Market Stability Reserve: Is Europe Serious about the Energy Union? - William Acworth; Nils May; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The European Union Emission Trading Scheme (EU ETS) has been implemented to provide a common climate policy instrument across European Union countries, to contribute to a credible investment perspective for low-carbon investors and support further European integration of energy markets. Thus the EU ETS is a key element of the European Energy Union.However, given the accumulation of a large surplus in the EU ETS, there is now a consensus between the EuropeanCommission, the European Council and the European Union Parliament (ENVI vote) that a Market Stability Reserve (MSR) needs to be implemented. The Latvian Presidency announced on March 26th a mandate to start trilogue negotiations onthe implementation of an MSR. Yet there remains discrepancy on the design parameters which will determine how quickly the MSR can respond to the surplus and restore consistency, price credibility, and robustness for investors of EU ETS.If Europe misses the opportunity to secure a timely restoration of EU ETS, then individual member states are likely to implement national measures to deliver energy and climate objectives. For example Germany has started to debate a Carbon Price add on for very carbon intensive power production to secure modernization and efficient power production should the EU ETS price not recover by the end of the decade. In this Roundup, we explore five design elements of the MSR that will determine the speed at which the most prominent European energy and climate policy instrument, the EU ETS, can deliver consistency, price credibility, and robustness for investors. The discussion of these design elements in the trilogue process that begins today will show how serious EU member states are not only about Climate Policy but equally about the Energy Union as a common policy framework to enhance investment and energy security across Europe.
Keywords: 330